2010
DOI: 10.1007/s11661-009-0118-5
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity of Phases and Growth Mechanisms in Peritectic Alloys Solidified at Low Speed: an X-Ray Tomography Study of Cu-Sn

Abstract: Abstract-The anisotropy of the solid-liquid interfacial energy plays a key role during the formation of as-solidified microstructures. Using the n-vector formalism of Cahn and Hoffman, this contribution presents the effect that anisotropy has on the equilibrium shapes of crystals and on surface tension equilibrium at triple lines. Consequences for heterogeneous nucleation of anisotropic crystals and for dendritic growth morphologies are detailed with specific examples related to Al-Zn and Zn-Al alloys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
(15 reference statements)
1
9
0
Order By: Relevance
“…4). This observation confirms the overlay growth mechanism evidenced by Kohler et al [11,12,16]: a new band of a does not necessarily needs to nucleate ahead of b, even in a small capillary, but can start from another a part of the specimen which is not in the section plane. After these bands, the various colors of the numerous a-grains present in the matrix of b (which has transformed into an (a + d) eutectoid) reveal that they have different crystallographic orientations.…”
Section: General Features Of the Specimenssupporting
confidence: 88%
See 1 more Smart Citation
“…4). This observation confirms the overlay growth mechanism evidenced by Kohler et al [11,12,16]: a new band of a does not necessarily needs to nucleate ahead of b, even in a small capillary, but can start from another a part of the specimen which is not in the section plane. After these bands, the various colors of the numerous a-grains present in the matrix of b (which has transformed into an (a + d) eutectoid) reveal that they have different crystallographic orientations.…”
Section: General Features Of the Specimenssupporting
confidence: 88%
“…Using a liquid metal cooling (LMC) Bridgman solidification setup with quench, these authors observed all three of the peritectic microstructures discussed above -lamellae, bands and islands -but their sample showed appreciable convection. Using synchrotron-based X-ray microtomography, Rappaz et al [16] confirmed a new growth mechanism of bands: a-and b-phases can be totally interconnected in three dimensions and bands (or islands) can result from an overlay mechanism, rather than from subsequent nucleation events. When the lateral growth of a new layer is too fast, an instability can lead to the formation of a lamellar structure as for eutectic alloys.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In recent years, two lines of development have added new details to this picture. A series of experiments have been performed on the peritectic alloy Cu-Sn [73,74,75]. In comparison to the alloys studied previously, Cu-Sn has a much larger solidification interval, which implies that extremely low growth rates have to be used to avoid morphological instabilities.…”
Section: Peritecticsmentioning
confidence: 99%
“…In order to reduce solutal convection as much as possible, capillary tubes were used. The microstructures were analyzed using standard metallography, EBSD, as well as post mortem X-ray tomography [74] to obtain a three-dimensional view (see Fig. 5).…”
Section: Peritecticsmentioning
confidence: 99%
“…Finally, it was found in experiments and by boundary integral simulations on the Fe-Ni system that coupled growth is stable only in certain ranges of concentrations and lamellar spacings [10]; at the boundary of this range, stable limit cycles of 1-k oscillations around the steady state were observed. Because of the limited stability, the initiation of coupled growth requires a non-trivial dynamical process, which generally leads to long transients before coupled growth emerges [8,17]. Since it is at present unknown how the stability conditions and the dynamics of the tran-sient depend on the characteristics of the phase diagram, more information on the initiation and stability of coupled growth in other alloy systems is needed.…”
Section: Introductionmentioning
confidence: 99%